Information Technology Outsourcing and The Impact to End User Productivity - Wah, Tuck Fui (2005)
Information Technology outsourcing have been growing at a phenomenal rate for the past few years. Companies have started focusing on core competencies and outsource the less critical activities of their value chains to outside vendors or suppliers. The often cited benefits of outsourcing are cost savings, operational expertise, staffing issues, flexibility to increase or decrease IT capacity. This study looks at the impact of Information Technology outsourcing at the people that actually uses the outsourced services, the end users to understand the impact to their productivity.